2012
DOI: 10.1177/0163443711427198
|View full text |Cite
|
Sign up to set email alerts
|

At the origin of a global industry: The TV format trade as an Anglo-American invention

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 11 publications
0
30
0
2
Order By: Relevance
“…Research by format scholars has revealed that PSBs have a long history of 'borrowing' programme ideas from abroad (Bourdon, 2012;Chalaby, 2012;Moran, 2013). Today the market is enforcing a system of intellectual property rights.…”
Section: Resultsmentioning
confidence: 99%
“…Research by format scholars has revealed that PSBs have a long history of 'borrowing' programme ideas from abroad (Bourdon, 2012;Chalaby, 2012;Moran, 2013). Today the market is enforcing a system of intellectual property rights.…”
Section: Resultsmentioning
confidence: 99%
“…The reasons behind this entertainment revolution are multiple and have been detailed elsewhere (Chalaby 2011(Chalaby , 2012. In an age of fierce competition, TV formats enable broadcasters to offer local programming -always the audience favourite -whilst managing risk (with the knowledge that the same concept has a proven track record in other markets) and driving down costs (through the progressive refinement of the production model).…”
Section: Jean K Chalabymentioning
confidence: 99%
“…scholarly works on transcultural remakes and adaptations of tV formats (including tV series) and their circulation are well established (Bataille & Hatchuel, 2012;Beeden & De Bruin, 2010;Bourdon, 2012;chalaby, 2012Esser, 2016;Ferrari, 2010;Holdsworth, 2011;Moran, 2009a;Navarro, 2012). Also, during the past few years, scandinavian tV series or films and their adaptations are the epicentre of research for many scholars who work on international format-travel (Gemzøe, 2013;Hochscherf & Philipsen, 2016;Perkins & Verevis, 2015;Waade, Nielsen, & Jensen, 2016).…”
Section: Introductionmentioning
confidence: 99%